2012
DOI: 10.1371/journal.pntd.0001829
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Morbidity and Hepatic Fibrosis in Mixed Schistosoma haematobium and S. mansoni Infections: A Population-Wide Study in Northern Senegal

Abstract: BackgroundThe global distribution map of schistosomiasis shows a large overlap of Schistosoma haematobium- and S. mansoni-endemic areas in Africa. Yet, little is known about the consequences of mixed Schistosoma infections for the human host. A recent study in two neighboring co-endemic communities in Senegal indicated that infection intensities of both species were higher in mixed than in single infections. Here, we investigated the relationship between mixed Schistosoma infections and morbidity in the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 49 publications
9
50
3
Order By: Relevance
“…However, children too young or small for MDA have considerable infection prevalences 5,6 in multiple African countries, where they can be exposed through bathing and other activities, 7,8 and they can be treated with no serious adverse events. [9][10][11][12][13] The morbidity pre-school-aged children (PSAC) experience from infection is not well defined, though: effects are known to include fecal occult bleeding, 14,15 hematuria, proteinuria, 16 ultrasound abnormalities, 17,18 and possibly anemia, 19,20 but clinical implications remain unclear. Thus, although these findings have prompted calls for including PSAC in MDA, 21 a 2010 WHO meeting concluded that more evidence was necessary.…”
Section: Introductionmentioning
confidence: 99%
“…However, children too young or small for MDA have considerable infection prevalences 5,6 in multiple African countries, where they can be exposed through bathing and other activities, 7,8 and they can be treated with no serious adverse events. [9][10][11][12][13] The morbidity pre-school-aged children (PSAC) experience from infection is not well defined, though: effects are known to include fecal occult bleeding, 14,15 hematuria, proteinuria, 16 ultrasound abnormalities, 17,18 and possibly anemia, 19,20 but clinical implications remain unclear. Thus, although these findings have prompted calls for including PSAC in MDA, 21 a 2010 WHO meeting concluded that more evidence was necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The milder form (LIP C) of portal fibrosis is normally seen in younger age groups. 6,35 In endemic areas, most people infected with S. mansoni present with LIP C and D forms of fibrosis, 36 whereas severe disease characterized with advanced fibrosis (LIPs E and F) is only observed in 5-10% of the people. 37 In our study population, advanced fibrosis characterized with LIPs E and F was recorded in 4.8% and 1.2% of the participants, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Senegal, a parasitological survey of 857 randomly chosen individuals from the S-SRV have identified bladder morbidity caused by schistosomiasis among 83% of the studied population, liver fibrosis among 27%, and both liver and bladder morbidity among 24% (Meurs et al, 2012). According to Wright (1972), about 25% of the Schistosoma's infected persons develop a disability that reduces their productive capacity.…”
Section: Schistosomiasismentioning
confidence: 99%